213k views
1 vote
Simplify (x-2)(x+6) using grouping and write the result expression in standard form

User Ben Groot
by
5.6k points

2 Answers

4 votes

Answer:

x^2 + 4x - 12.

Explanation:

(x - 2)(x + 6)

= x(x + 6) - 2(x + 6)

= x^2 + 6x - 2x - 12

= x^2 + 4x - 12.

User Mador
by
5.0k points
5 votes

Answer:

(x + 2)(x + 6)

= x(x + 6) + 2(x + 6)

= x ∙ x + 6x + 2x + 2 ∙ 6(Distribute the terms.)

= x2 + 6x + 2x + 12

= x2 + 8x + 12(Combine like terms.)

Step-by-step explanation: don't put this all!!! just put the answer. This is plato answer!!!! I copied it so don't put it all, just put x2 + 8x + 12

User Colonder
by
5.1k points